Analisis Manfaat Penggunaan Aplikasi Zoom Dalam Pembelajaran Daring Bagi Guru Dan Siswa Di Sekolah Dasar - Kuntarto, Eko; Sofwan, Muhammad; Mulyani, Nurlaili (JURNAL PENDIDIKAN DASAR NUSANTARA, 2021)
This study aims to describe the benefits of using the zoom app in online learning for teachers and students in elementary schools. The type of research in this study is qualitative research with phenomenological type. The sample in this study was 8 informants, consisting of two grade v teachers and six vc grade students. Benefits for teachers include making it easier to achieve learning objectives, facilitating interaction with students, providing variations in online learning, creating active online learning, while the benefits of using zoom for students include making it easier to understand materials, improving the spirit of online learning, eliminating the boredom of online learning. The benefits felt by teachers and students have a positive impact in online learning so that it becomes more effective